Use of Electrodeposition of Nickel in the Manufacture of Leu Annular Targets - Cifuentes-Molina, G (Sociedad Chilena de Quimica, 2013)
This work presents the results of a thin electroplated layer of nickel on the surface of the uranium to achieve deposits 15 to 25 ?m thick. Ultrasound tests and electron microscopy showed good adhesion and homogeneity of the Ni deposit, which has high hardness and relatively small grain size, with an orientation in the direction of current flow.